2022
DOI: 10.1007/s10067-022-06254-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of lysine crotonylation and 2-hydroxyisobutyrylation reveals significant features of systemic lupus erythematosus

Abstract: Introduction/objectives To seek significant features of systemic lupus erythematosus (SLE) by utilizing bioinformatics analysis. Method Liquid chromatography-tandem mass spectrometry (LC–MS/MS) was used to quantify lysine crotonylation (Kcr) and lysine 2-hydroxyisobutyrylation (Khib) in peripheral blood mononuclear cells (PBMCs) of systemic lupus erythematosus (SLE) patients and normal controls. Results Seventy-six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The genes annotated to these five cannabis use-associated CpGs are relevant to a range of health outcomes. [34][35][36][37][38][39][40][41][42][43][44] The five epigenome-wide significant CpGs are annotated to the nearest genes: LINC01132, ADGRF1, ADAM12, ACTN1, and APOBR. Of these, cg01101459-LINC01132, cg00813162-ACTN1, and cg14237301-APOBR were inversely associated with cannabis use, meaning that individuals who had used cannabis had lower DNAm at these CpG sites compared to those who had never used cannabis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes annotated to these five cannabis use-associated CpGs are relevant to a range of health outcomes. [34][35][36][37][38][39][40][41][42][43][44] The five epigenome-wide significant CpGs are annotated to the nearest genes: LINC01132, ADGRF1, ADAM12, ACTN1, and APOBR. Of these, cg01101459-LINC01132, cg00813162-ACTN1, and cg14237301-APOBR were inversely associated with cannabis use, meaning that individuals who had used cannabis had lower DNAm at these CpG sites compared to those who had never used cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…35 Genetic variants and differential expression of the ACTN1 have been reported in various diseases, including congenital macrothrombocytopenia, Angelman syndrome, Bowen disease, postmenopausal osteoporosis, lupus erythematosus, and COVID-19. [35][36][37][38]47,48 APOBR (Apolipoprotein B receptor) encodes a receptor protein that binds to dietary triglyceride-rich lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Figure E shows the demographic differences between SLE individuals and healthy subjects. From earlier investigations conducted by our lab team, a more comprehensive list of the study population is available . Every participant signed informed consent before being included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have shown that this modification also occurs in nonhistone proteins in various compartments of cells. To date, K hib modification has been identified in human or animal [9][10][11][12][13], fungus (Aspergillus flavus [14], Fusarium graminearum [15], Candida albicans [16], bacteria (Proteus mirabilis [17] and Toxoplasma gondii [18]) and plants. All these studies indicate that K hib modification is not only widely present in various organisms, but also involved in a wide variety of physiological functions.…”
Section: Introductionmentioning
confidence: 99%